(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
The Public Employee Performance Management Information System (PEPMIS) was introduced in Tanzania to strengthen employee performance management across the public service. Despite wide implementation, limited attention has been given to how Human Resource (HR) practitioners experience the system within everyday institutional contexts. This study examined practitioner experiences across five dimensions: system usability, organisational support, user competence and training, technical challenges, and effectiveness in supporting the full performance management cycle. Guided by the Technology Acceptance Model and the Job Demands–Resources Theory, a qualitative interpretivist design was employed, using semi-structured interviews with twenty-five purposively selected HR professionals. Findings reveal that usability is undermined by slow responses, complex navigation, and inconsistent functionality. Organisational support is weakened by limited leadership involvement, poor coordination, and inadequate technical assistance. User competence is compromised by insufficient practical training, while technical challenges stem from weak infrastructure and unreliable connectivity. Although PEPMIS enhances documentation and transparency, its effectiveness is undermined by a misalignment between system demands and institutional capacity. The study concludes that effective digital performance management requires stronger organisational commitment, improved infrastructure, and sustained user capacity development.